Monthly bulletin - Bŭlgarska narodna banka. (Bulgarian National Bank, 1994)
Continues: News bulletin (Bŭlgarska narodna banka).Continued in part by: Commercial banks in Bulgaria 1311-4824.With annual report (January 1996 - June 1997).